Implementation Of Mediator-Based Integration System For A Transparent Access To Multiple Biological Databases. - Husain, Wahidah; Anwar, Muhammad Fairuz (2007)
Existing biological databases seem to function independently from each other. Different organizations and research group, build customised databases with different formats for collecting biological data through their research.